Song Pak: capstone - Pak, Song, artist (Colorado State University. Libraries, 2024)
The artist's statement: Whether it be an event poster, a product, or an illustrated book, I like to create a work that engages the audience. Whatever my illustration is for, I hope it brings the viewer into a little world of their own. Whimsy, imagination, and playfulness are all words I would use to describe my style. If you love brands such as Sanrio, Pokemon, or any other brands that have cutesy characters, I am the illustrator/designer for you. I work mostly digital. My main mediums with the computer are Procreate, Indesign, and Illustrator. Color, composition, and typography are very important to me in creating a cohesive brand and narrative.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design